Monomelic Amyotrophy (Hirayama Disease) with Proximal Upper Limb Involvement: A Case Report - Mamun, Abdullah Al; Sheikh, Mirazul Islam; Bala, Chandra Shekhar; Islam, Tariqul; Alam, Md Badrul (Journal of National Institute of Neurosciences Bangladesh, 2018)
Monomelic amyotrophy is an uncommon, benign, unilateral disorder of the lower motor neurons, affecting predominantly the hand and forearm muscles. A 28-year-old man presented with insidious-onset, slowly progressive, unilateral weakness and atrophy of his shoulder girdle and arm muscles on right side. A neurological examination revealed weakness and atrophy in his right deltoid, infraspinatus, supraspinatus and triceps muscles. Electromyography demonstrated an active and chronic neurogenic pattern affecting his right C5 and C6 myotomes; magnetic resonance imaging of his cervical spine showed snake eye appearance within the spinal cord. Upper limb proximal form of monomelic amyotrophy is a rare clinical entity with a wide differential diagnosis. Physicians, especially neurologists, should be familiar with this benign condition to avoid inappropriately labeling patients as having amyotrophic lateral sclerosis and other disorders with less favorable outcomes. Journal of National Institute of Neurosciences Bangladesh, 2018;4(1): 63-66